EKSPLORASI DIRI DALAM KARYA SERIGRAFI - Drs. Irwan, M.Sn., AGUSNEDI SAPUTRA, Yofita Sandra, S.Pd., M.Pd., (Serupa The Journal of Art Education, 2017)
The creation of this final work aims at how to visualize human as a person, need to learn from the barrage of effort in understanding the nature of themselves. And camouflage the feelings that are then packaged in graphic artwork and stand out the various expressions and explore all possible shapes along with the original character of a particular object.The methods and processes that used in the creation of this graphic art through several stages: a) preparation, b) Elaboration c) Synthesis d) Realization e) FinishingFrom this graphic artwork can be concluded that Along with the sense and awareness about the openness of the weaknesses of a human is a benchmark for a change. Summarizes all past valuable experiences as well as current activities and future expectations into a unified image.Keywords: Self Exploration, Serigraphy